Comparison of treatment effects from total arch distalization using modified C‐palatal plates versus maxillary premolar extraction in Class II patients with severe overjet. (16th June 2021) - Alfawaz, Fawaz; Park, Jae Hyun; Lee, Nam‐Ki; Bayome, Mohamed; Tai, Kiyoshi; Ku, Ja Hyeong; Kim, Yoonji; Kook, Yoon‐Ah
Abstract: Introduction: This study aimed to compare the skeletodental and soft tissue changes with total arch distalization using a modified C‐palatal plate (MCPP) and maxillary first premolar extraction treatment in Class II malocclusion patients with severe overjet. Setting and sample population: The sample consisted of 46 adult patients who had Class II Division 1 malocclusion with severe overjet; 25 of them received non‐extraction treatment with MCPPs (age, 22.5 ± 7.2 years), and 21 received maxillary first premolar extraction treatment (age 23.4 ± 6.5 years). Method: A total of 26 variables were measured on pre‐ and post‐treatment lateral cephalograms. To evaluate the differences between pretreatment and post‐treatment in each group, t tests and Wilcoxon rank‐sum tests were used. To compare the amount of change between the two groups, MANOVA test was used. Results: The overjet was significantly reduced in the MCPP and extraction groups by 4.8 mm and 5.4 mm, respectively. However, the two groups had no significant difference in the sagittal, vertical and angular changes of the maxillary incisors. In addition, regarding soft tissue changes, the MCPP and extraction groups showed an increased nasolabial angle of 7.5° and 9.4°, decreased upper lip to the true vertical line of 1.8 mm and 2.2 mm, respectively ( P  < .001). Conclusions: There was no significant difference in the skeletal changes between the MCPP and extraction groups, and the reduction in overjet was similar in the groups. These results suggest that MCPP might be a viable treatment option for total arch distalization in Class II malocclusion patients with severe overjet.